The Analysis of The Influence of Work Environment and Job Stress on Employee Performance With Work Commitment As A Mediating Variable at The Regional Development Planning, Research and Development Agency Office in Kotamobagu City - Balak, Vanesa Anastasia; Lengkong, Victor P.K.; Worang, Frederik G. (Abdurrauf Science and Society, 2025)
The Regional Development Planning, Research and Development Agency Office in Kotamobagu City are a technical institution tasked with implementing regional planning, research and development activities to improve regional development planning, enhance the regional innovation system and increase the utilization of research and development results for achieving regional development goals. The purpose of this study is to analyze the influence of Work Environment and Work Stress on Employee Performance, with Work Commitment as a mediating variable at the Office of Regional Development Planning, Research, and Development Agency of Kotamobagu City. The analytical method used is a quantitative approach with an associative method, utilizing SmartPLS version 4.0. he research results indicate that the Work Environment and Work Stress have a direct positive influence on Employee Work Commitment. Furthermore, Work Stress and Work Environment affect Employee Performance through the mediating role of Work Commitment; however, this mediating effect is positive but not statistically significant for employees at the Regional Development Planning, Research, and Development Agency of Kotamobagu City.